PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS III SDN 002 KUOK - Muhammad Syahrul Rizal; Syahrilfuddin '; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Research drop was triggered by low the students learn math class III 002 SDN Kuok 59,34, with an average grade of the mathematical value KKM set school is 70.Of 23 people students only 8 students reached KKM. This research is research the act of aiming to increase class learned mathematics student using model of learning cooperative type Think Pair Share ( TPS ).The formulation of problems in this research is “whether the application of a model of learning cooperative type tps learning about mathematics student can improve the results of the class III SDN 002 Kuok”.The subject of this research is a student of class III SDN 002 Kuok which consisted of 23 people students.Design this research is research the act of a class composed of four stages on cycles, namely planning, the exercise of, observation and reflaksi.This research carried out on june 25 April 2014 until May 23 2014 with 3 cycles. Thesis presenting the results of this study obtained from the value of daily deut. before the act of with an average 59,34. In cycles 79,40, i rose to on a cycle II 88,95, with the average increase again while in cycles III student average declined to 79,09. Activity in the teacher a learning process in cycles I first meeting 69,44 % and the second increased to 80,55 %.The cycle II first meeting 83,33 % and the second increased to 88,88 %.The cycle III the first meeting of 91,66 % and in the second increased to 94,44 %. he result analysis of data activity students on cycle I first meeting 69,44 % and second meeting increased to 77,77 %Cycle II first meeting 77,77 % and increase at second meeting be 86,11 %.Cycle III in the first meeting 88,88 % and in the second increased to 91,66 %.Based on explanation above showed kind of classroom cooperative type Think Pair Share( TPS ) can increase learned mathematics students class III SDN 002 Kuok.Keywords:Cooperative, Think Pair Share ( TPS ), The Result of Learning about Mathematics